1998
DOI: 10.1136/bjo.82.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of topographic measures of the glaucomatous optic nerve head

Abstract: Aims/background-Laser scanning tomography provides an assessment of three dimensional optic disc topography. For the clinical purpose of follow up of glaucoma patients, the repeatability of the various measured variables is essential. In the present study, the reproducibility of morphometric variables calculated by the topographic scanning system, TopSS (Laser Diagnostic Technology, San Diego, CA) was investigated. Methods-Two independent measurements (30 minutes apart) each consisting of three complete images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
6

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
0
11
0
6
Order By: Relevance
“…It has been reported that the results obtained from this system are highly reproducible (Geyer et al 1998). In the current study, one author drew the contour of the optic disc without any patient information, which eliminated intra-observer variation affecting the results.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It has been reported that the results obtained from this system are highly reproducible (Geyer et al 1998). In the current study, one author drew the contour of the optic disc without any patient information, which eliminated intra-observer variation affecting the results.…”
Section: Discussionmentioning
confidence: 82%
“…Of the 12 variables that can be investigated by TopSS, we focused on the volume below, the half-depth area and the average cup depth, as it has been indicated by Geyer et al that these three variables show a high level of reproducibility and are reliable parameters for detecting small changes (Geyer et al 1998). Although TopSS A can access the disc every 30 degrees, we decided that it would be adequate to sum up the raw data for every quadrant portion.…”
Section: Investigated Disc Variablesmentioning
confidence: 99%
“…So far, SLO-studies have mainly evaluated the usefulness of optic disc parameters for glaucoma detection, their reproducibility of measurements and any correlations with visual field defects. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, relatively little attention has been paid to the possible value of SLO optic disc biometry for improvement of glaucoma follow-up. [20][21][22] To reliably detect development or progression of disease with a certain measurement parameter, it is necessary to know the absolute difference between follow-up measurements that must be exceeded to detect a statistically significant change over time.…”
Section: Introductionmentioning
confidence: 99%
“…Entre esses novos métodos de imagem, destacam-se a análise da camada de fibras nervosas da retina por meio da Polarimetria de Varredura a Laser (GDx, Laser Diagnostic Technologies, San Diego, CA, USA) (6)(7) , e a topografia de disco óptico, realizada pelo Tomógrafo Retiniano de Heidelberg (HRT, Heidelberg Engineering, Heidelberg, Germany) (8)(9) ou o Topógrafo de Disco Óptico (TOPSS, Laser Diagnostic Technologies, San Diego, CA, USA) (10)(11) . As informações estruturais provenientes dos instrumentos relacionados acima podem ser validadas através da comparação com métodos diagnósticos considerados como "gold standard" em glaucoma.…”
unclassified
“…Apesar do TOPSS e HRT usarem o mesmo princípio na aquisição das imagens (Sistema de Varredura Confocal), existem diferenças quanto às variáveis testadas em cada aparelho (11,18) , e na forma de delinear o disco óptico para proceder a análise. Portanto, as informações obtidas com o HRT não podem ser extrapoladas e utilizadas como premissas para o TOPSS.…”
unclassified